Development of the Motor Functions in 7-15-year-old Children: The Czech National Study - Rudolf Psotta; Jan Hendl; Jakub Kokštejn; Gabriela Jahodová; Milan Elfmark (Karolinum Press, 2015)
The aim of the national study was to assess the development of motor functions in the population of the Czech children. A Czech representative sample of 7-15-year-old children (n = 1076) was assessed on fine manual coordination, gross motor coordination and balance using the Movement Assessment Battery for Children-2 (MABC-2). Concurrently, the cross-cultural validity of the MABC-2 was examined on a basis of the comparison of results of the testing to the test performance reported for the United Kingdom sample. Unimanual and bimanual coordination, and visuomotor coordination associated the aiming and timing interceptive tasks improved up to 12-15-year-old children. The Czech girls demonstrated the mature static balance at the age of 7 years, while the Czech boys by two years later. The study showed that the MABC-2 can be a valid method for assessment of gross motor coordination in the Czech children. Before use of this test battery in research and educational and clinical practice in the Czech Republic, an adjustment of the norms of the manual dexterity and balance tests is needed.